KARAKTERISTIK SPEKTRAL ELEKTROMAGNETIK SPECIES DOMINAN PADA HUTAN RAWA GAMBUT KALIMANTAN TENGAH (Electromagnetic Spectral Characteristics of Dominant Species at the Peat-Swamp Forest at Central Kalimantan): Hendrik Segah1*, Freddy Wijaya1, Laju Gandharum2 dan Hiroshi Tani3 - Admin JHT (Jurnal Hutan Tropika, 2015)
ABSTRACTThis paper reports the results of the spectral library from dominant trees in peat-forest in Central Kalimantan, Indonesia supported under JST-JICA Project: “Wild Fire and Carbon Management in Peat Forest in Indonesia”. Spectral libraries are commonly established as a means to archive representative signatures of natural materials. Such signatures can then be used to train feature extraction and classification algorithms applied to remote sensing data imagery. Spectral analyses were performed to the 33 dominant species in peat-forest in Central Kalimantan, Indonesia obtained during the field survey measurement (in-situ measurements) and airborne campaign by HYMAP sensor in 2011-2014. We found, each vegetation type has unique spectral signature or characteristics. The shapes of reflectance spectra can be used for identification of vegetation types combine with remote sensing data (airborne and satellite images). Keywords: Spectral library/signature, Peat-Forest, Spectroradiometer, Vegetation and Kalimantan